Study On Gen Z phycology Over Growth Of Business By Use Of Social Media Marketing In Small And Medium Scale Business In Ahmedabad City - Rishi, Mahadik; Harshad, Parmar; Vidani, Dr. Jignesh (Contemporary Journal of Applied Sciences, 2024)
This paper talks about the psychology of Gen Z and how it would influence the growth of SMBs in Ahmedabad through social media marketing. In it, demographic variables such as age, education level, occupation, and social media behavior were investigated using a quantitative approach to derive some relevant correlations for creating the marketing strategy. Thus, the study sheds light on the need for companies to adopt specific marketing strategies that match people's preferences, which are trademarks of this generation, termed quite tech-savvy. This generation likes authentic, interactive, and purpose-driven brand experiences; therefore, SMES must enhance its social media presence by developing exciting content for those who use those media. Practical implications of such findings reveal proper usage of consumer insights towards increasing brand and retention